Methodological foundations of political-geographical studies of borders using the example of Hungary - Mađar Ede (Glasnik Srpskog Geografskog Društva)
This paper explores how political geography, through the application of various methodological approaches, studies borders. Political geography analyzes how political systems, decisions, and institutions influence the organization of space and territorial control. Borders, as qualitative lines that separate territories, can be linear or zonal and are classified by morphology, physiognomy, genesis, and functions. The example of Hungary reveals how historical changes in borders, such as natural, national, and treaty boundaries, impact the political and economic aspects of the state. Border management involves control of movement, security, and cross-border cooperation, which is critical for regional stability and development. Hungary has historically frequently changed its borders, necessitating active international cooperation and diplomacy to resolve issues and promote stability and economic growth.